Management Accountant Ethics on Earning Management Practices in the Character of Ulul’Azmi Prophets - Nor Rahma Rizka; Tjiptohadi Sawarjuwono (Jurnal Akuntansi dan Pajak, 2023)
This study aims to review the literature and reflect on the ethics of management accountants on earning management activities in the character of Ulul‘Azmi Prophets. This study uses library research with data sourced from reputable journals such as Elsevier Science Direct, Emerald, Scopus, Google Scholar, books and other articles relevant to the research topic. This paper shows that the character of Ulul‘Azmi Prophets can be the right philosophy for strengthening the ethics of management accountants especially in earning management activities. This is because of the nature of the Ulul‘Azmi Prophets who are based on faith and strong firmness in holding principles.